2020
DOI: 10.1029/2019ea000946
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Author Diversity and Acceptance Rates and Citations in Peer‐Reviewed Earth Science Manuscripts

Abstract: The scientific community is becoming more demographically diverse, and team science is becoming more common. Here, we compare metrics of success in academic research, acceptance rates, and citations, among/across differing team compositions regarding demographic diversity. We collected the final decisions and citations as of 2019 of 91,427 manuscripts submitted from 2012-2018 to journals published by the American Geophysical Union. We matched the authors by email on each manuscript to self-provided demographic… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(43 citation statements)
references
References 35 publications
0
33
0
Order By: Relevance
“…Pervasive racism in science also drives substantial and systemic biases in publication rates, citation rates, and editorial positions [24]. Publication-related metrics show distinct patterns of bias against racially and/or ethnically diverse scientific teams, which experience more than 5% lower acceptance rates and fewer citations than less diverse author teams [41]. Citational segregation-where authors prefer citing authors from the same racial/ethnic group(s)-has been demonstrated with white authors citing other white authors more frequently [24].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
See 1 more Smart Citation
“…Pervasive racism in science also drives substantial and systemic biases in publication rates, citation rates, and editorial positions [24]. Publication-related metrics show distinct patterns of bias against racially and/or ethnically diverse scientific teams, which experience more than 5% lower acceptance rates and fewer citations than less diverse author teams [41]. Citational segregation-where authors prefer citing authors from the same racial/ethnic group(s)-has been demonstrated with white authors citing other white authors more frequently [24].…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
“…Many efforts to improve diversity in science disciplines have not yet been successful [46][47][48][49]. In fact, gender and racial citation biases remain stable or have even worsened over the last half century [16,[21][22][23][24]41,50], highlighting that efforts to change the system have, by and large, failed to remove systemic biases. Clearly, assessing scientific impact, and thereby assigning value to an individual's scientific contribution, exclusively-or even primarilythrough citations of peer-reviewed literature reflects and amplifies the existing numerous biases that remain embedded within science.…”
Section: Pivoting the Paradigm To Ensure Equitable Evaluation In Science (1) Citation Counts Are Biasedmentioning
confidence: 99%
“…A separate analysis comparing author groups and acceptance rates across AGU journals for the same time period (Lerback et al, 2020) shows that the acceptance rates and citations of papers with gender‐diverse and internationally diverse author groups are higher than those for single‐gender author teams and single‐country author teams. This result in the Earth and Space Sciences, which supports results from other studies in other disciplines (Nielsen et al, 2017; reviewed in Hall et al, 2018), indicates that forming diverse teams leads to better and more impactful science.…”
Section: Discussionmentioning
confidence: 99%
“…Here we focus on the unique author networks rather than team size, persistence, or other dynamics. A related paper examines the relation between these networks and acceptance rates and citations in AGU journals (Lerback et al, 2020).…”
Section: Approachmentioning
confidence: 99%
“…Taking Gini Impurity as measure of diversity and number of citations received within 5 years of publication as measure of scientific impact, they found, using regression analysis and randomized baseline models, that ethnic diversity is positively correlated with scientific impact. Lerback et al (2020), using data for submissions and publications across all American Geophysical Union (AGU) journals, found that diversity in USA-based author teams regarding race/ethnicity (as identified by selfprovided demographic information within the AGU's membership database) is associated with lower acceptance rates and citation rates. However, more studies, using data from different sources and different disciplines, on ethnic diversity are needed especially for understanding the causes behind the relationship between ethnic diversity and scientific impact.…”
Section: Introductionmentioning
confidence: 99%